Instructional teaching strategies for reducing Malay negative transfer errors in learning mandarin vocabulary for Malay learners - Lee, Hui Ling (2022)
Problem of negative transfer always affect L3 learners in learning the target language. Furthermore, the negative transfer errors often encountered by L3 learners are also linked to ineffective teaching strategies. In view of this, the purpose of this study seeks to identify the occurrences of negative transfer errors of Malay language committed by non-Chinese learners in their Mandarin vocabulary learning. Next is to investigate the selected instructional teaching strategies in order to in improve the L3 learners’ negative transfer errors. To this end, the perspectives of non-Chinese learners towards the selected instructional teaching strategies are also be investigated as to assess its’ effectiveness in improving negative transfer problem. A total of 100 participants from four Mandarin level two classes are selected in this study. Qualitative measures are generated through the methods of document analysis, interview, observation and written diaries, are used to collect and analyze data. The findings of this study indicate that: (1) a total of 1,170 negative transfer errors are group into four types: improper usage of words, word orders error, improper usage of collocation and improper usage of culture images; (2) all of the nine teaching strategies are very helpful in improving the learners’ problems of negative transfer; (3) for the most preferred teaching strategies, four strategies such as ‘recitation’, ‘compare and contrast’, ‘note-taking and summarizing’, and ‘role play’ are chosen. In contrary, for the least-preferred teaching strategy, ‘non-linguistic representation’ is chosen; (4) ‘cues, questioning and activating prior knowledge’ is view as the most interesting teaching strategy; whereas ‘recitation’ is view as the least interesting teaching strategy; (5) ‘recitation’ is also chosen as the most challenging teaching strategy; and (6) ‘homework and practice’ is chosen as the most effective teaching strategy; whereas both of the strategies of ‘role play’ and ‘non-linguistic representation’ are chosen as the least effective teaching strategy. These findings imply the betterment of the combination of the nine teaching strategies enrich the current body of knowledge in the field of foreign language teaching and learning.